Case of the Diffuse Form of Xanthogranulomatous Pyelonephritis. (9th January 2013) - Yoshino, Tateki; Moriyama, Hiroyuki
Abstract : Xanthogranulomatous pyelonephritis (XGP) is a rare entity and constitutes less than 1% of chronic pyelonephritis. A 71-year-old male was introduced to our department with general malaise and abnormal findings of computed tomography (CT). Abnormal findings of complete blood count and laboratory examination included an elevated WBC count and C-reactive protein. Urinalysis showed combined hematuria and pyuria, and Escherichia coli was detected in urine culture. Abdominal CT revealed left hydronephrosis with staghorn renal calculi and thin cortex of the left kidney. Because of poor condition, the patient underwent construction of the left nephrostomy. After that, the remission of the inflammation was achieved. Several months after the construction, frequent obstructions of nephrostomy catheter because of turbid urine and intermittent fever elevation were observed. The patient and his family desired left nephrectomy despite his poor condition in general. Surgical dissection was very difficult due to fixed mass. Not long after that the patient died due to sepsis and cardiovascular failure. Microscopic findings of the left kidney revealed infiltration of lymphocytes and lipid-laden macrophages (xanthoma cells) corresponding to XGP.